Does "live high-train low and high" hypoxic training alter stride mechanical pattern during repeated sprints in elite team-sport players? - Girard, O.; Millet, G. P.; Brocherie, F. (International Journal of Sports Physiology and Performance, 2024)
Purpose We examined changes in stride temporal parameters and spring-mass model characteristics during repeated sprints following a 3-week period of "live high-train low and high" (LHTLH) altitude training in team-sport players.